Structural modification of siRNA for efficient gene silencing - Lee, So Jin; Son, Sejin; Yhee, Ji Young; Choi, Kuiwon; Kwon, Ick Chan; Kim, Sun Hwa; Kim, Kwangmeyung (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Small interfering RNA (siRNA) holds a great promise for the future of genomic medicine because of its highly sequence-specific gene silencing and universality in therapeutic target. The medical use of siRNA, however, has been severely hampered by the inherent physico-chemical properties of siRNA itself, such as low charge density, high structural stiffness and rapid enzymatic degradation; therefore, the establishment of efficient and safe siRNA delivery methodology is an essential prerequisite, particularly for systemic administration. For an efficient systemic siRNA delivery, it is a critical issue to obtain small and compact siRNA polyplexes with cationic condensing reagents including cationic polymers, because the size and surface properties of the polyplexes are major determinants for achieving desirable in vivo fate. Unfortunately, synthetic siRNA is not easily condensed with cationic polymers due to its intrinsic rigid structure and low spatial charge density. Accordingly, the loose siRNA polyplexes inevitably expose siRNA to the extracellular environment during systemic circulation, resulting in low therapeutic efficiency and poor biodistribution. In this review, we highlight the innovative approaches to increase the size of siRNA via structural modification of the siRNA itself. The attempts include several methodologies such as hybridization, chemical polymerization, and micro- and nano-structurization of siRNA. Due to its increased charge density and flexibility, the structured siRNA can produce highly condensed and homogenous polyplexes compared to the classical monomeric siRNA. As a result, stable and compact siRNA polyplexes can enhance serum stability and target delivery efficiency in vivo with desirable biodistribution. The review specifically aims to provide the recent progress of structural modification of siRNA. In addition, the article also briefly and concisely explains the improved physico-chemical properties of structured siRNA with respect to stability, condensation ability and gene silencing efficiency. (c) 2012 Elsevier Inc. All rights reserved.
Keywords: IN-VIVO DELIVERY; RNA INTERFERENCE; CHEMICAL-MODIFICATION; THERAPEUTIC APPLICATIONS; MAMMALIAN-CELLS; NANOPARTICLES; EFFICACY; PEI; POLYETHYLENIMINES; OLIGONUCLEOTIDES